Strategi Marketing Mix Berbasis Syariah Meningkatkan Loyalitas Pelanggan - Rusli Siri; Rahmi Rahmi; Andi Faisal Syam (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This research is motivated by the phenomenon of the industrial era that pursues maximum profit by justifying all means without considering sharia values. As a result, competition becomes unfair and detrimental to consumers, and can even cause companies to lose customers. The developing paradigm considers sharia-based business behavior to hinder the achievement of maximum profit. Therefore, the marketing mix from an Islamic perspective includes products, prices, promotions, distribution, and people as strategies in maintaining competitiveness. This study uses a qualitative method with a phenomenological approach, where researchers explore the essence of human experience related to the phenomenon of sharia marketing mix, and instill it. The results show that sharia-based marketing mix strategies contribute to the development of the marketing world. This approach not only pursues worldly benefits, but also hereafter benefits. Divine values ​​(rabbaniyah) are the main basis, while the morals of marketers also determine the blessings of the business. Marketers are also required to uphold integrity and use common sense in implementing marketing strategies. Customer loyalty is an important element that needs to be developed, accompanied by the instillation of tauhid values ​​in products. Thus, marketers do not only perform business functions, but also carry out Islamic practices. In conclusion, sharia marketers who implement marketing mix principles based on the Qur'an and Sunnah are able to provide benefits to customers and create long-term, sustainable relationships between consumers and companies.